(untitled) (Global Journal of Management and Business Research, 2012)
This article underlined on the recognition of the organization development. Regarding being on the threshold of knowledge and wisdom era, the article also shed light on concepts like learning organization and the issue of organization development in knowledge-based era and reviews its perquisites and some effecting elements in modern era.